2021
DOI: 10.1037/cps0000023
|View full text |Cite
|
Sign up to set email alerts
|

Harmful treatments in psychotherapy.

Abstract: The potential for psychological treatments to result in harmful outcomes is underexamined. This special issue highlights important areas for consideration in putative harmful interventions in clinical psychology. The range of potential harmful interventions includes specific protocols, deviations from evidencebased approaches, misapplication of evidence-based interventions, and applications of interventions that lack underlying mechanisms for targeted problems. It is hoped that this special issue will begin a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…across mental disorders). [12][13][14][15] However, various studies have underscored the relevance of investigating potential harms in clinical trials on psychological treatments. For instance, one study found that about 93% of individuals treated with psychotherapy for obsessive-compulsive disorder reported experiencing at least one adverse event during treatment.…”
mentioning
confidence: 99%
“…across mental disorders). [12][13][14][15] However, various studies have underscored the relevance of investigating potential harms in clinical trials on psychological treatments. For instance, one study found that about 93% of individuals treated with psychotherapy for obsessive-compulsive disorder reported experiencing at least one adverse event during treatment.…”
mentioning
confidence: 99%
“…Another grave feature is the bizarre treatment interventions that a few participants reported. While the psychotherapy field is moving in an evidence-based direction, there still seem to be some psychotherapists who use nonscientific methods that could be potentially harmful (McKay & Jensen-Doss, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This allows therapists not only to track progress (and potential side effects) on an individual level but also to measure the variability of change as a function of patient characteristics, treatment interventions, therapists, and clinics/services (Barkham & Lambert 2021). For example, on an aggregated level, the data can serve to investigate side effects, treatment dosage, therapist effects, and clinic effects (e.g., McKay & Jensen-Doss 2021). The session-by-session assessment structure is accompanied by statistical and methodological developments to analyze the nested structure of longitudinal data (e.g., Raudenbush & Bryk 2002).…”
Section: Session-by-session Assessmentsmentioning
confidence: 99%